Cohort profile: the clinical 'Psoriasis in Adolescents' (PIA) cohort in Denmark. Issue 9 (24th September 2019) - Blegvad, Christoffer; Andersen, Anne-Marie Nybo; Groot, Jonathan; Zachariae, Claus; Skov, Lone
Abstract : Purpose: Psoriasis is a chronic inflammatory skin disease that frequently debuts in childhood and adolescence. We wished to determine environmental and genetic risk factors for the development of psoriasis in children and adolescents, as well as to investigate debut type, trigger factors, course of disease, nature and influence of stress related to both child and family and risk factors for comorbidity. The 'Psoriasis in Adolescents' (PIA) cohort will provide data on the relationship between psoriasis and, respectively, genetic disposition, early-life exposures, quality of life and comorbidity. Participants: The PIA cohort is nested in the large general population Danish National Birth Cohort (DNBC). We invited 390 adolescents with psoriasis and corresponding maternally predisposed and non-predisposed controls. Participants underwent an interview and a clinical examination consisting of a skin inspection and physical measurements including blood sampling and microbiological swabs. Additionally, four self-administered questionnaires on physical and mental health were completed. Findings to date: The final PIA cohort consists of 81 adolescents with psoriasis, 110 parentally predisposed and 124 non-predisposed psoriasis-free adolescents. The validity of the maternally reported psoriasis status from the DNBC was found to be low on clinical examination (47.5%). In contrast, the self-reported psoriasis status of the DNBC mothers was clinically confirmed in 80.8% of the cases. Future plans: The PIA cohort offers the possibility of assessing the clinical characteristics, course of psoriasis and development of comorbidities in adolescents with clinically confirmed disease from a general population. Comparison with predisposed and non-predisposed controls is possible and genetic analyses are scheduled. We plan to invite the participants for a follow-up in 5–10 years. Furthermore, we plan to include newly diagnosed adolescents with psoriasis from the 18-year DNBC follow-up. All information is linkable on the individual level with data from the DNBC and nationwide registries in Denmark.